Aeroacoustic simulation of broadband sound generated from a cross-flow fan using immersed boundary-lattice Boltzmann method. Issue 1 (1st April 2022) - Kusano, K; Furukawa, M; Sakoda, K; Fukui, T
Abstract: In this study, we investigated the capability of the immersed boundary-lattice Boltzmann method (IB-LBM) in simulating the broadband sound generated from a cross-flow fan. The present method is based on the lattice Boltzmann equation with the D3Q27 particle velocity model, and the cascaded collision operator was used to stably simulate high-Reynolds-number flows. Furthermore, the direct-forcing approach was used to consider rotating blades in the regular lattice. To capture turbulence eddies in the rotor, we used a high-resolution grid that contained approximately 340 million nodes. The simulation successfully captured the fundamental flow features of the cross-flow fan such as the eccentric vortex, and the simulation results were consistent with the experimental results in terms of the time-averaged velocity distribution at the outlet of the fan. In addition, by resolving turbulent eddies in the impeller, the simulation successfully predicted the broadband sound spectrum in the frequency range of 2 kHz or less.